Βέλτιστος δομικός και ενεργειακός σχεδιασμός - Αναγνωστάκη, Καλλιόπη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής, 2015)
The first objective of this study is to present an optimization algorithm for reducing the initial cost of construction in the structural design phase of buildings. Another scope of this study is to present design guidelines for reducing CO2 emissions and environmental cost associated with structural materials. While, basic constraint is the satisfaction of the structural design codes. In this study, the proposed methodology based on the Differential Evolution strategy, a simple metaheuristic algorithm for global optimization. Application of the method is illustrated by three simple examples of sizing optimization. The improvement of energy efficiency in buildings is among the first priorities worldwide. To complete this task, more than 400 different measures are available, and the designer has to be prepared to face a problem with several conflicting goals such as energy, financial, environmental impact and other factors. In this way, the decision maker approaches the problem as multiple objectives and in order to solve it, he uses the weighted sum method. To investigate the situation further, a modeling approach is proposed under realistic conditions so the designer may be able to evaluate its performance and to study the alternative scenarios. Concluding, the solution is represented by the Pareto front curve which is the geometric locus of all Pareto optimum solutions.